Pemanfaatan teknologi komunikasi dan informasi di perpustakaan - Naila Naila (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2018)
This article discusses the rapid development of information technology, demands librarians and librarians to struggle and work harder in developing knowledge, skills and expertise in the fields of libraries, documentation and information, as well as information technology. Information and Communication Technology is a large umbrella terminology that includes all technical equipment for processing and conveying information. keywords: communication technology, information technology